Phenotypic and Genetic Characterization of Temperature-Induced Mutagenesis and Mortality in Cupriavidus metallidurans - Van Houdt, Rob; Vandecraen, Joachim; Heylen, Wietse; Leys, Natalie; Monsieurs, Pieter; Provoost, Ann; Aertsen, Abram (Frontiers in Microbiology, 2021)
Cupriavidus metallidurans strains display a decreased viability when incubated in rich medium at a temperature of 37°C compared to their normal growth temperature of 30°C. A phenomenon coined “temperature-induced mortality and mutagenesis” (TIMM). To scrutinize this aberrant phenotype further, the contribution of specific inducers and protective agents were determined. Different growth media, including Lysogeny Broth (LB) and Schatz, and components, including casamino acids, particular amino acids (proline, cysteine, glycine, glutamine, leucine, histidine and phenylalanine) and ammonium, were found to induce TIMM at 37°C. Sorbitol was found to counteract TIMM. Furthermore, although TIMM is well-conserved within the C. metallidurans species, multiple and strain-specific TIMM-inducers exist. Twenty nine percent of the TIMM survivors inherited resistance to TIMM. Whole-genome sequencing of two resistant derivatives revealed an important role of an uncharacterized oxidoreductase, indicating putative metabolic poisoning when grown in high concentration nitrogen-containing media at 37°C.